Hubungan Pemberian MP-ASI dan Pendidikan Ibu dengan Stunting Pada Balita di Puskesmas Yosomulyo Lampung - Elsa Silvia Fitriani; Maryati Sutarno (Universitas Malahayati, 2025)
ABSTRACT Stunting is a chronic condition that describes stunted growth due to malnutrition over a long period of time. In 2022, Yosomulyo Community Health Center was found to experience stunting of 7.69% and in 2023 it was 8.45%, which indicates an increase in stunting among toddlers. Several factors include early provision of MP-ASI and low education. To find out the relationship between providing MP-ASI and maternal education with stunting in toddlers at the Yosomulyo Lampung Community Health Center in 2024. Quantitative analytical research with a cross sectional design. The research sample of mothers with toddlers consisted of 84 respondents using a simple random sampling technique. Secondary data using a checklist sheet was analyzed using the square test. The results of univariate analysis showed that the majority of toddlers did not experience stunting, 69.0%, 65.5% were given MP-ASI 6 months and 57.1% had high maternal education. The results of the bivariate analysis showed a relationship between giving MP-ASI (p value = 0.000) and maternal education (p value = 0.000) with stunting in toddlers. Providing MP-ASI and maternal education are associated with stunting in toddlers.Keywords: Giving MP-ASI, Mother's Education, Stunting in Toddlers ABSTRAK Stunting/pendek merupakan kondisi kronis yang menggambarkan terhambatnya pertumbuhan karena malnutrisi dalam jangka waktu yang lama. Puskesmas Yosomulyo tahun 2022 ditemukan yang mengalami stunting sebesar 7,69% dan tahun 2023 sebesar 8,45% yang menandakan terjadi peningkatan stunting pada balita. Beberapa faktor diantaranya pemberian MP-ASI dini dan pendidikan yang rendah. Mengetahui hubungan pemberian MP-ASI dan pendidikan ibu dengan stunting pada balita di Puskesmas Yosomulyo Lampung tahun 2024. Penelitian analitik kuantitatif dengan rancangan cross sectional. Sampel penelitian ibu yang ibu yang memiliki balita berjumlah 84 responden dengan teknik simple random sampling. Data sekunder menggunakan lembar cheklist dianalisis menggunakan uji uji square. Hasil analisis univariat diketahui sebagian besar balita tidak mengalami stunting 69,0%, pemberian MP-ASI 6 bulan 65,5% dan pendidikan ibu tinggi 57,1%. Hasil analisis bivariat ada hubungan antara pemberian MP-ASI (p value = 0,000) dan pendidikan ibu (p value = 0,000) dengan stunting pada balita. Pemberian MP-ASI dan dan pendidikan ibu berhubungan dengan stunting pada balita. Kata Kunci: Pemberian MP-ASI, Pendidikan Ibu, Stunting pada Balita